Family Practice Nursing in Newfoundland and Labrador: Are Reported Roles Reflective of Professional Competencies for Registered Nurses in Primary Care?. (October 2021) - Mathews, Maria; Ryan, Dana; Buote, Richard; Parsons, Sandra; Lukewich, Julia
Background: Family practice nurses are Registered Nurses who work collaboratively in primary care and deliver a range of services. Professional competency statements have been developed to describe the skills and knowledge of family practice nurses as a distinct field. Purpose: We conducted a secondary analysis of qualitative interview data to examine how family practice nurse roles/activities relate to recently developed professional competencies. Methods: Family physicians and family practice nurses in Newfoundland and Labrador (NL) participated in semi-structured interviews, during which they discussed roles/activities and scope of practice surrounding family practice nursing. For this secondary analysis, we used competency statements to inform thematic coding of the transcribed interviews. Results: For the initial study, a total of 8 participants (5 family practice nurses; 3 family physicians) were interviewed from diverse practices. All transcripts from the original study (n = 8) were included in the secondary analysis and analysed across 47 competencies encompassing 6 domains (Professionalism; Clinical Practice; Communication; Collaboration and Partnership; Quality Assurance, Evaluation and Research; Leadership). Roles/activities reported by participants were reflective of the competencies, but with substantial variation in expression. Conclusions: Family practice nursing competency statements reflect the actual activities of family practice nurses in NL. The professional competencies can serve as a framework to examine contributions of family practice nurses and identify areas warranting further training. The use of competencies to explore family practice nurses' roles and activities can assist with optimizing scope of practice.